2005
DOI: 10.1016/j.ymthe.2004.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in vivo inhibition of CNS neurodegeneration by Bcl-XL gene transfer

Abstract: The inherently low regenerative capacity of the CNS demands effective strategies to inhibit neurodegeneration in acute lesions but also in slowly progressive neurological disorders. Therefore, therapeutic targets that can interact with the degeneration cascade to block, not just postpone, neuronal degeneration need to be defined. Bcl-X(L), a protein protecting the integrity of the mitochondrial membrane potential, was investigated for its neuroprotective properties in a long-term in vivo model of neuronal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 44 publications
3
81
0
2
Order By: Relevance
“…Transcript expression was monitored for several genes known to have important roles in RGC death after axotomy. 5,[6][7][8]26,27 Quantitative real-time reverse transcriptase-PCR (qRT-PCR) on whole retinas was conducted at 7 days after axotomy, a time when RGC apoptosis is well underway but before these cells are lost. 3,8 First, mRNA expression in naive healthy retinas was compared with axotomized control retinas that had been treated with control siRNA against firefly luciferase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcript expression was monitored for several genes known to have important roles in RGC death after axotomy. 5,[6][7][8]26,27 Quantitative real-time reverse transcriptase-PCR (qRT-PCR) on whole retinas was conducted at 7 days after axotomy, a time when RGC apoptosis is well underway but before these cells are lost. 3,8 First, mRNA expression in naive healthy retinas was compared with axotomized control retinas that had been treated with control siRNA against firefly luciferase.…”
Section: Resultsmentioning
confidence: 99%
“…Kv1.1 depletion increased mRNA expression of Bcl-X L , a molecule that protects the mitochondrial membrane potential and is neuroprotective for injured RGCs. 27 Note that RGCs comprise only B7% of retinal cells and 25-50% of RGCs degenerate by 7 days; 2,3,24 thus, transcript changes in individual RGCs are likely underrepresented.…”
Section: Discussionmentioning
confidence: 99%
“…85 This demonstrates that in delivering neurotrophic factors that protect RGCs from death, preservation of retinal function must also be considered. AAV-mediated delivery of the gene encoding an antiapoptotic protein, Bcl-X L , allows survival of more than 40% of RGCs 8 weeks after optic nerve crush (compared with 15% in sham-treated eyes), 86 and combining this with AAV.GDNF delivery potentiates the treatment effect such that 67% of RGCs survive. 87 Damage to the optic nerve and loss of RGCs are also features of multiple sclerosis, which can be modelled in mice by inducing experimental allergic encephalomyelitis, using systemic sensitization with spinal emulsion.…”
Section: Vector-mediated Neuroprotection and Modulation Of Ocular Angmentioning
confidence: 99%
“…4 Thus, several studies focused at the maintenance of mitochondrial integrity by overexpression of antiapoptotic members of the Bcl-2 family of proteins. [5][6][7] This strategy proved to be significantly more efficient than caspase inhibition, although in long-term studies substantial neuronal cell loss was still observed. 5,8 Neurotrophic factors used in traumatic lesion paradigms only shortly postponed neuronal degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] This strategy proved to be significantly more efficient than caspase inhibition, although in long-term studies substantial neuronal cell loss was still observed. 5,8 Neurotrophic factors used in traumatic lesion paradigms only shortly postponed neuronal degeneration. 9,10 Glial cell line-derived neurotrophic factor (GDNF) is a promising candidate in the long-term treatment of Parkinson's disease, although recent clinical trials demonstrated divergent outcomes.…”
Section: Introductionmentioning
confidence: 99%